Information Seeking Behavior of Darul Qur'an Mulia Islamic Boarding School Students in Determining Higher Education Study Programs - Noer Haslinda; Alfida Alfida (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
This study aims to determine the level of information-seeking behavior of students in SMA Class XII Pesantren Terpadu Darul Qur'an Mulia in determining the study program in higher education. This type of research is descriptive research with a quantitative approach. The population of this study amounted to 204 students of Class XII Pesantren Terpadu Darul Qur'an Mulia, and the sample was taken by purposive sampling technique using the Slovin formula, so that a sample of 67 students was obtained. This research uses Kuhlthau's 1993 Information Search Process (ISP) model. Kuhlthau's theory has six stages including initiation, selection, exploration, formulation, collection, and presentation. The results showed that the information seeking behavior of students in determining the study program in higher education was classified as good. This can be seen from each stage of the Kuhlthau model, most students experience feelings, thoughts and actions that are in accordance with the Kuhlthau model, namely: Initiation gets a score of 3.27 (Very Good), Selection gets a score of 3.12 (Good), Exploration got a score of 2.92 (Good), Formulation got a score of 3.12 (Good), Collection got a score of 3.06 (Good) and Presentation got a score of 3.22 (Good). Santri experience all the stages that exist in the Kuhlthau model, especially at the Initiation stage, both in feelings, thoughts, and actions taken. Meanwhile, at the exploration stage, students tend not to feel the feeling to stop searching and the inconsistency of information as according to Kuhlthau's model. Based on the results of the study, the information seeking behavior of students in determining the study program in higher education as a whole is at a good level by obtaining a score of 3.11 (Good).